Promotion Mix Optimization: A Case Study of BPR Bank Gresik - Tita Hayuning Sukma; Moh. Agung Surianto; Al Kusani Al Kusani (INNOVATION RESEARCH JOURNAL, 2023)
This research aims to evaluate and analyze the promotional mix used in an effort to increase the number of credit customers at the BPR Bank Gresik Regional Public Company. This research uses a descriptive qualitative method approach. Data was collected through interviews, documentation and observation from several informants. Data triangulation was carried out to ensure the accuracy and validity of the findings. The results of the research show that the Perumda BPR Bank Gresik Credit Account Officer uses a promotional mix, namely personal sales, advertising, sales promotions, public relations and direct marketing. The findings of this research indicate that the application of the promotional mix that has been carried out by Credit Account Officers is classified as less than optimal due to several obstacles, such as limited time divided between promotions and the credit application analysis process, tight competition with commercial banks and cooperatives, lack of understanding by Credit Account Officers regarding features. social media.